2005
DOI: 10.1103/physreve.71.062902
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale multifractality analysis of a 12-lead electrocardiogram

Abstract: This paper proposes that a multiscale multifractality (MSMF) method be adopted for the spatiotemporal analysis of 12-lead ECG. By using this method, the authors find that, in some frequency range, 12-lead ECG has a more complex fractal structure, and the position of the largest singularity strength range delta alpha is not relying on the data length but on the scale factor. By determining the inflexion, the MSMF proves to be more sensitive in displaying the trend that the singularity strength range delta alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…Δα is a measure of the deviation from monofractal, indicating the degree of multifractality. Smaller Δα indicates that the measure tends to be monofractal, and contrarily, larger Δα indicates multifractality [12] .…”
Section: Multifractal Singularity Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Δα is a measure of the deviation from monofractal, indicating the degree of multifractality. Smaller Δα indicates that the measure tends to be monofractal, and contrarily, larger Δα indicates multifractality [12] .…”
Section: Multifractal Singularity Spectrummentioning
confidence: 99%
“…Physiologic signals generated by complex self-regulating systems, such as heartbeat interval, electrocardiogram, gait etc. have been proven to be multifractal, and the degree of multifractality often relates to pathological state or natural aging process [10][11][12] . The multifractal formalism has been applied to EEG analysis recently [13,14] .…”
mentioning
confidence: 99%
“…and the abnormal lead multifractal singularity spectrum can denote the heart disease region. In 2005, Wang et al [47] proposed an expanded multifractal analysis method, viz. multiscale multifractality (MSMF), for the spatio-temporal analysis of physiologic time series.…”
Section: Chaos and Fractal Analysis In Electrocardiogram Researchmentioning
confidence: 99%
“…In that study, the authors examined the distributions of entropy measures with scale factors from HRV signals in healthy young and healthy elderly subjects, and found that at some scale factor or within a certain range, the nonlinear parameter resulted in better discrimination. Wang et al [20] also proposed the multiscale multifractality (MSMF) method, and examined the distribution of singularity strength range with scale factor from ECG of 65 healthy humans. Our studies [21] pointed out that the essence of multiscale analysis is just to change the sampling frequency of the signals, and then explore them at diversified time levels.…”
mentioning
confidence: 98%